Friction stir welding of carbon nanotubes reinforced Al-Cu-Mg alloy composite plates. Issue 9 (September 2017) - Zhao, Ke; Liu, Zhenyu; Xiao, Bolyu; Ma, Zongyi
Abstract: Carbon nanotubes (CNTs) reinforced Al-Cu-Mg composite plates of 2.2 mm in thickness after extrusion and T4 treatment were joined by friction stir welding (FSW) and the joint efficiency reaches 87%. There was no precipitate in both heat-affected zone (HAZ) and nugget zone (NZ) as a medium rotation rate of 800 rpm and a relative high travel speed of 100 mm min −1 were used. In the NZ, FSW disarranged the alignment of CNTs to random orientation and dispersed CNT uniformly. The orientation of CNTs perpendicular to the tensile direction and the possible dissolution of solute clusters made the HAZ become the weakest zone in the joint leading to the failure in the HAZ.